INTEGRASI NILAI-NILAI ISLAM DALAM PENDIDIKAN MODERN DI SMK KESEHATAN AISYIYAAH BIMA - Muhammad Irfan (Program Studi Manajemen Pendidikan Islam, 2023)
Modern education in the era of globalization demands a balance between science and moral values. The integration of Islamic values in modern education is an important aspect in shaping the character of students who have noble morals and are professional in their fields. This study aims to analyze the application of Islamic values in the education system at SMK Kesehatan 'Aisyiyah Bima and its impact on students. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the integration of Islamic values is carried out through the curriculum, school culture, and teacher role models. The curriculum at SMK Kesehatan 'Aisyiyah Bima combines Islamic material in health learning, such as ethics in medical services and honesty values in health practices. In addition, school culture such as congregational prayer, reading the Qur'an, and the habituation of discipline and responsibility also strengthen Islamic values in students' daily lives. The implication of this integration is the creation of a religious and professional educational environment, as well as graduates who not only have skills in the health sector but also have a strong Islamic character. Therefore, the integration of Islamic values in modern education at Health Vocational Schools is an effective strategy in creating a competent and moral generation